2022
DOI: 10.1001/jamapediatrics.2022.1296
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High-Need Education-Based Funding and School Suspension Rates for Autistic Students in New Zealand

Abstract: IMPORTANCE Autistic students often experience poor educational outcomes that have implications for later life, including unemployment, interactions with the criminal justice system, increased risk for substance abuse, and low socioeconomic status. Improving educational outcomes is critical for ensuring that autistic young people can reach their potential.OBJECTIVE To quantify differences in suspension rates between autistic and nonautistic students and to assess whether high-need education-based funding for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…For example, a recent study suggested that a more targeted support for autistic students receiving ORS funding in Aotearoa New Zealand was associated with decreased suspension rates. 41 The findings of this study would suggest a systematic undercount of autistic Pasifika children and a number of Pasifika children and families not receiving the health care and support they are entitled. It is highly likely that those who face longer terms of undiagnosed or misdiagnosis could lead to poorer long-term outcomes in all facets of life such as social and adaptive functioning which could affect education outcomes as well as employment.…”
Section: Discussionmentioning
confidence: 78%
“…For example, a recent study suggested that a more targeted support for autistic students receiving ORS funding in Aotearoa New Zealand was associated with decreased suspension rates. 41 The findings of this study would suggest a systematic undercount of autistic Pasifika children and a number of Pasifika children and families not receiving the health care and support they are entitled. It is highly likely that those who face longer terms of undiagnosed or misdiagnosis could lead to poorer long-term outcomes in all facets of life such as social and adaptive functioning which could affect education outcomes as well as employment.…”
Section: Discussionmentioning
confidence: 78%
“…Pharmaceutical codes such as chemical and formulation IDs can identify specific types of dispensed medications. Pharmaceutical data will be used for case identification only when a particular type of medication is used exclusively or predominantly to treat an outcome of interest, consistent with previous studies using IDI data to identify specific health outcomes 43–47. However, as it is impossible to determine why an individual received a particular medication, we cannot rule out the possibility that a medication was dispensed for a condition separate from our outcome of interest.…”
Section: Methods and Analysismentioning
confidence: 90%
“…The research team has a history of producing robust, high-impact research using IDI data 43–46. Therefore, we anticipate this study will produce several manuscripts targeted towards high-impact journals.…”
Section: Discussion and Disseminationmentioning
confidence: 99%
“…In the absence of any national registries for NDDs in NZ, previously established IDI-based methods will be used to identify cases of NDDs using a combination of diagnostic data and pharmaceutical dispensing (Bowden et al, 2020a(Bowden et al, , 2020b. These methods remain formally unvalidated; however, they have been applied in extant literature with demonstrated face validity (Bowden et al, 2020c(Bowden et al, , 2022McLay et al, 2021McLay et al, , 2022. Physical and psychometric health surveillance measures contained in the B4SC data set, together with demographic attributes, will be combined with the aim to 1.…”
Section: Introductionmentioning
confidence: 99%